Evidenzbasierte Therapieempfehlungen für das familiäre Mittelmeerfieber - Kallinich, Tilmann; Blank, Norbert (Zeitschrift für Rheumatologie, 2019)
BackgroundFamilial Mediterranean fever (FMF) in Germany is a rare, genetically linked disease of childhood and adolescence, which is characterized by recurrent febrile episodes and clinical signs of peritonitis, pleuritis and arthritis. Treatment with colchicine is effective and well-tolerated in the majority of patients; however, some patients do not sufficiently respond to this treatment or are intolerant to colchicine. For these patients first-line treatment with biologics which block interleukin-1 can be used.ObjectiveThe aim was to formulate evidence-based treatment recommendations for patients with an insufficient response and intolerance to colchicine treatment.MethodsBased on a literature search and the European League Against Rheumatism (EULAR) recommendations on FMF from 2016 the appointed members of the Society for Pediatric and Adolescent Rheumatology (GKJR) and the German Society for Rheumatology (DGRh) convened to work out and form a consensus in a joint statement on evidence-based treatment recommendations on FMF.ResultsAfter intensive discussions all decisions were in concordance. A total of 5 superordinate principles and 10 recommendations were agreed upon.DiscussionThe joint activities of the GKJR and the DGRh were successfully concluded in a timely manner. The recommendations form a good basis for optimal treatment of all age groups of patients with FMF.
Gesehen am 19.11.2019